Some foundations for multiplicative habits models - Ryoji Hiraguchi (The Johns Hopkins University, Department of Economics, 2004)
While consumption models with multiplicative habits are becoming increasingly popular, some important theoretical questions about these models have not yet been addressed. This paper fills three such gaps: Existence of an optimal consumption path; satisfaction, by that path, of the consumption Euler equation; and convergence of that path to the stationary (steady state) path.
Keywords: 330; Wachstumstheorie; Gesamtwirtschaftlicher Konsum